Analisis Keterkaitan Antara Aktivitas Kendaraan Bermotor dengan Tingkat Kebisingan: Studi Kasus di Jalan Gatot Subroto, Kota Palu - Kadir, A.I.N.K.; Marjan, M.; Alricha, A.; Patunrangi, S. N. J.; Amaludin, M. B. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
The elevation of mobility in Palu has evolved into a new noise issue. Noise from motorized vehicles has quite an impact on the tranquility of areas that directly intersect with the highway. Gatot Subroto Axis Road is an instance of a congested road as public facilities such as educational institutions take the crowd of the area. The study aims to analyze the relationship of vehicle activities toward noise level at Gatot Subroto. The research method uses field measurement by a sound level meter (SLM), tripod, and counter. Noise sampling standards refer to SNI 8427:2017 regarding measuring environmental noise levels. Data was collected for one day on weekdays and weekends with three take times at three sampling points. Noise level analysis is carried out using frequency distribution. The next data analysis is to look for the equivalent noise level or LAeq. The noise level points varied between 71,6 dBA-84,02 dBA. The traffic volume reached a peak at 853. The p-value was 0,72 which was above 0,05. The regression test was Y=0,0048x+72,904, and R2 showed 0,15 points, which means that 15% of the noise level was affected by traffic volume. In conclusion, the average noise level at Gatot Subroto Axis Road exceeded the quality standards set according to the Decree of the Minister of State for the Environment No. 48 of 1996, which is 55 dB(A). Despite no significant difference in noise levels on weekdays and weekends based on the t-test, the noise level is affected by traffic volume. Noise from motorized vehicles has quite a big impact on the tranquility of areas that directly intersect with the highway. he limitation of this research is the limited amount of data due to the small number of research points and the insufficient number of days, so further research is needed.